2022
DOI: 10.21203/rs.3.rs-1687679/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimates of prevalence of anti-SARS-CoV-2 antibodies among blood donors in South Africa in March 2022

Abstract: In line with previous instalments of analysis from this ongoing study to monitor ‘Covid Seroprevalence’ among blood donors in South Africa, we report on an analysis of 3395 samples obtained in mid-March 2022 from all provinces of South Africa – a timepoint just after the fourth (primarily omicron) wave of infections. As in our previous analyses, we see no evidence of age and sex dependence of prevalence, but significant variation by race. Differences between provinces have largely disappeared, as prevalence ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 2 publications
3
13
1
Order By: Relevance
“…Nonetheless, these example estimates (Table S4) are consistent with reported serology measures [4 th column vs. e.g. ∼90% seropositive in March 2022 after the Omicron BA.1 wave reported in Bingham et al 2022 (8)] and reinfection rates reported elsewhere [5 th and 6 th columns vs. e.g., reported much higher reinfection rate during the Omicron wave in Pulliam et al (9)].…”
Section: A Proposed Approach To Compute the Reinfection Rates Using M...supporting
confidence: 86%
“…Nonetheless, these example estimates (Table S4) are consistent with reported serology measures [4 th column vs. e.g. ∼90% seropositive in March 2022 after the Omicron BA.1 wave reported in Bingham et al 2022 (8)] and reinfection rates reported elsewhere [5 th and 6 th columns vs. e.g., reported much higher reinfection rate during the Omicron wave in Pulliam et al (9)].…”
Section: A Proposed Approach To Compute the Reinfection Rates Using M...supporting
confidence: 86%
“…The reduced mortality in the Omicron BA.4/BA.5 wave was more specifically presumed to be related to the high prevalence of humoral and cell-mediated immunity in South Africa. Studies of humoral immunity reported SARS-CoV-2 antibody sero-prevalence estimates of 71% (26) and 73% (3) before the Omicron BA.1/BA.2 wave, while estimates after the Omicron BA.1/BA.2 wave but just before the Omicron BA.4/BA.5 wave were 97% (27) and 91% (28). The latter serosurvey indicated that 61% of individuals had serological evidence of SARS-CoV-2 infection during the Omicron BA.1/BA.2 wave in South Africa (28).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with ongoing affinity maturation of responses after second antigenic exposures (28). In South Africa, where >95% of people are now estimated to be seropositive, this scenario of hybrid immunity is likely very common (17,29). However, even in the context of these high titer responses, BA.4 shows reduced sensitivity to neutralization compared to other VOCs, perhaps accounting for ongoing community transmission.…”
Section: Discussionmentioning
confidence: 99%